Identification of Vicia Species Native to South Korea Using Molecular and Morphological Characteristics - Han, Seahee; Sebastin, Raveendar; Wang, XiaoHan; Lee, Kyung Jun; Cho, Gyu-Taek; Hyun, Do Yoon; Chung, Jong-Wook (Frontiers in Plant Science, 2021)
Recently, within the Fabaceae family, the Vicia genus has been recognized for its vital role in sustainable agriculture. Vicia species are economically important grain and forage crops. However, the presence of complex morphological characteristics makes identification and recognition of native species difficult. In this study, the possibility of using DNA barcoding regions (ITS2, matK, and rbcL) to distinguish among 19 Vicia taxa (59 accessions) found in Korea was evaluated. The sequence alignment analysis revealed considerable nucleotide diversity (π) between the loci, in which ITS2 showed the highest mean interspecific distance whereas there was no intraspecific variability among the barcode regions in 12 of the 19 taxa. Phylogenetic analysis of combined barcoding regions revealed well-resolved phylogeny with the highest species level discrimination. Combinations of barcode loci were also used in classification at the subgenera and section levels. The results revealed that the combined barcoding regions can be used effectively to differentiate the following species: V. angustifolia var. segetilis, V. bungei, V. villosa, V. cracca, V. dasycarpa, V. hirsuta, V. tetrasperma, V. amurensis, V. hirticalycina, and V. chosenensis. However, it is difficult to differentiate the species of V. unijuga, V. unijuga var. kaussanensis, V. linearifolia, V. unijuga f. angustifolia, V. nipponica, V. amoena, V. venosa var. cuspidata, V. pseudo-orobus, and V. japonica with the tested barcode regions. These species come under sect. Vicilla are found to be closely related or species that have recently undergone speciation, thus, it has limitation to distinguish with recommended barcodes. Hence, to differentiate the unclassified species, 39 morphological characteristics were investigated, in which 16 useful characteristics were selected for efficient classification. Finally, the 16 selected morphological useful traits efficiently differentiated all the Vicia species. In conclusion, combination of barcoding loci together with morphological characteristics of this study efficiently discriminated all the Korean Vicia species.